Determining the Effects of Increasing Levels of Xylanase in Nutrient Adequate Diets on Growth Performance, Carcass Characteristics of Growing-Finishing Pigs - H. R. Kerkaert; J. M. DeRouchey; S. S. Dritz; R. D. Goodband; M. D. Tokach; J. C. Woodworth; H. Calderone Cartagena; M. Gonçalves (Kansas Agricultural Experiment Station Research Reports, 2019)
A total of 1,944 mixed sex growing-finishing pigs (PIC; 337 × 1050; initial BW of 49.9 ± 1.18 lb) were used in a 131-d growth trial to determine the effects of increasing added xylanase xylanase in adequate diets on grow-finish pig growth performance and carcass characteristics. Pens were assigned to 1 of 6 treatments in a randomized complete block design with BW as a blocking factor. There were 12 replicate pens per treatment and 27 pigs per pen. The experimental diets were corn-soybean meal-based and were fed in 5 phases. The 6 dietary treatments were formulated to: 0, 2.3, 4.5, 9.1, 18.1, and 34.0 of enzymatic activity for xylanase (IU)/lb (0, 5, 10, 20, 40, and 75 IU/kg) of added xylanase (Belfeed B 1100 MP; Jefo Nutrition, Inc., Saint-Hyacinthe, Quebec). From d 0 to 70, there was a tendency (quadratic,P= 0.068) for average daily gain (ADG) to decrease and then increase with increasing added xylanase, but there was no evidence(P>0.10) of differences for average daily feed intake (ADFI) and feed efficiency (F/G). From d 70 to 131 and overall, there was no evidence of difference (P>0.10) observed for ADG, ADFI, and F/G. There was no evidence for difference (P>0.10) between treatments for number of pigs receiving injectable treatments or mortalities. For carcass traits, increasing xylanase increased then decreased (quadratic,P= 0.010) percentage carcass yield. Also, as xylanase increased, percentage lean decreased (linear,P= 0.038) and backfat marginally increased (linear,P= 0.066). In conclusion, adding increasing levels of xylanase in nutrient adequate diets did not impact growth performance or mortality but did improve carcass yield at intermediate levels.
Keywords: finishing pig; growth performance; xylanase